2022
DOI: 10.3390/polym14030614
|View full text |Cite
|
Sign up to set email alerts
|

From Strain Stiffening to Softening—Rheological Characterization of Keratins 8 and 18 Networks Crosslinked via Electron Irradiation

Abstract: Networks of crosslinked keratin filaments are abundant in epithelial cells and tissues, providing resilience against mechanical forces and ensuring cellular integrity. Although studies of in vitro models of reconstituted keratin networks have revealed important mechanical aspects, the mechanical properties of crosslinked keratin structures remain poorly understood. Here, we exploited the power of electron beam irradiation (EBI) to crosslink in vitro networks of soft epithelial keratins 8 and 18 (k8–k18) filame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…This properties can be related to the fact that disulfide bonds of keratin was broken following oxidative extraction of keratin and its stiffness is dependent on the side chain chemical groups. It was previously revealed that, for keratin, the strands joining between thick bundles is fragile [60], this weak coupling results more strand slipping under forces and thus does not follow strain stiffening.…”
Section: Discussionmentioning
confidence: 99%
“…This properties can be related to the fact that disulfide bonds of keratin was broken following oxidative extraction of keratin and its stiffness is dependent on the side chain chemical groups. It was previously revealed that, for keratin, the strands joining between thick bundles is fragile [60], this weak coupling results more strand slipping under forces and thus does not follow strain stiffening.…”
Section: Discussionmentioning
confidence: 99%
“…This is possibly due to the fact that the GWLC model is designed to explain mutual interactions between filaments in a homogeneous, entangled network of semiflexible polymers. The limitations of the GWLC have been demonstrated in previous studies on networks of the cytoskeletal intermediate fila-ment keratin 15,24,34 and were explained with network architectures which were incompatible with the prerequisites of the theory. We suspect that the inability to account for the jump for the 6 base-pair crosslinkers in this case has a similar cause.…”
Section: Temperature-dependent Variation Of Plateau Modulusmentioning
confidence: 97%
“…22 In relation to the engineering of biomaterials, chemical crosslinking, for example via electron beam radiation, can also be used to permanently alter and crosslink collagen networks. [23][24][25] Reconstituted networks of filamentous actin (F-actin) are experimentally well-characterized and were used as an ideal for the development of theoretical models. 9,12,16,21,26,27 The concentration-dependent scaling of the elastic plateau modulus, G 0 ∝ c 7/5 , for entangled F-actin solutions is theoretically described within the frame of the tube model 28 and has been experimentally verified.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 4 shows the experimental data obtained for (a) keratin gel, 52 (b) silk fibroin gel, 24 (c) neurofilament-based hydrogel, 22 Table 1 Here, n e , q c and DE are parameters obtained from a fit procedure of eqn (2) to the experimental data extracted from ref. 21, where the stress-strain of samples of PEG hydrogels with different hydrophobic ratios r are presented.…”
Section: Application To Biopolymer-based Hydrogelsmentioning
confidence: 99%